Differential Responsiveness of Monocyte and Macrophage Subsets to Interferon. Issue 1 (10th December 2019) - Han, Shuhong; Zhuang, Haoyang; Lee, Pui Y.; Li, Mingjia; Yang, Lijun; Nigrovic, Peter A.; Reeves, Westley H.
Abstract : Objective: Peripheral blood mononuclear cells (PBMCs) in systemic lupus erythematosus (SLE) patients exhibit a gene expression program (interferon [IFN] signature) that is attributed to overproduction of type I IFNs by plasmacytoid dendritic cells. Type I IFNs have been thought to play a role in the pathogenesis of SLE. This study was undertaken to examine an unexpected influence of monocyte/macrophages on the IFN signature. Methods: Proinflammatory (classic) and antiinflammatory (nonclassic) monocyte/macrophages were sorted from mice and analyzed by RNA sequencing and quantitative polymerase chain reaction (qPCR). Type I IFN‐α/β/ω receptor (IFNAR‐1) expression was determined by qPCR and flow cytometry. Macrophages were stimulated in vitro with IFNα, and pSTAT1was measured. Results: Transcriptional profiling of peritoneal macrophages from mice with pristane‐induced SLE unexpectedly indicated a strong IFN signature in classic, but not nonclassic, monocyte/macrophages exposed to the same type I IFN concentrations. Ifnar1 messenger RNA and IFNAR surface staining were higher in classic monocyte/macrophages versus nonclassic monocyte/macrophages ( P < 0.0001 and P < 0.05, respectively, by Student's t ‐test). Nonclassic monocyte/macrophages were also relatively insensitive to IFNα‐driven STAT1 phosphorylation. Humans exhibited a similar pattern: higher IFNAR expression ( P < 0.0001 by Student's t ‐test) and IFNα‐stimulated gene expression ( P < 0.01 by paired Wilcoxon's rank sum test) in classic monocyte/macrophages and lower levels in nonclassic monocyte/macrophages. Conclusion: This study revealed that the relative abundance of different monocyte/macrophage subsets helps determine the magnitude of the IFN signature. Responsiveness to IFNα signaling reflects differences in IFNAR expression in classic (high IFNAR) compared to nonclassic (low IFNAR) monocyte/macrophages. Thus, the IFN signature depends on both type I IFN production and the responsiveness of monocyte/macrophages to IFNAR signaling.